Kaynak Maliyetli Dönemsel Rezervasyon Çizelgeleme: Bir Matematiksel Modelleme Yaklaşımı - Uğur Eliiyi (İzmir İktisat Dergisi, 2021)
In this study, a novel optimization problem for simultaneous capacity planning and scheduling in reservation scheduling environments is proposed. The problem is important for seasonal reservation systems such as hotel or seat reservations of travel agencies, or operation and treatment reservations in health tourism. The objective of the problem is to maximize the net profit gained from the processed reservations. To the best of our knowledge, the problem was not previously studied. An integer programming model is developed for exact solutions and extensive computational experimentation reveals model performance under different scenarios. The results are analyzed, and managerial implications are discussed.